Phytoremediation of chromium: distribution and speciation of chromium in Typha angustifolia (International Journal of Plant Biology, 2017)
Chromium (Cr), especially in hexavalent chromium [Cr(VI)] may contaminate water or soil and cause detrimental effects, as it is potentially carcinogenic and teratogenic. Phytoremediation using plants such as Typha angustifolia provides an alternative approach for handling Cr waste. The objective of this study was to determine the mechanism of Cr accumulation in T. angustifolia. Hydroponic media containing T. angustifolia was added with 0, 1, 5, 10 and 20 ppm of Cr (VI) (K2Cr2O7). After 15 days of treatment, distribution and speciation of Cr in roots and shoots of T. angustifolia were analyzed using XAS and μ-XRF. Results showed that Cr was detected in almost all parts of root and shoot at different intensities. Intensities of Cr was higher in roots (especially in the vascular bundle) than in shoot. Cr speciation in the root and shoot was found as trivalent chromium [Cr(III)] which formed as a result of Cr(VI) reduction. Based on the patterns of Cr distribution and speciation, results of this study suggest that T. angustifolia in this study does not reduce Cr(VI) to become Cr(III) inside the plants.